Overview of the Granting of Marriage Dispensation for Minors (Study on the Determination of the Rantauprapat Religious Court Number 62/Pdt.P/2017/Pa.Rap) - Siska Wahyuni; Toni Toni (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Marriage is something that is commanded by Allah SWT and the Messenger, in which there is wisdom, including being able to bring inner peace and prevent people from committing immorality. Underage marriages require a dispensation application submitted by the applicant/parents for a legal marriage requirement and supported by evidence of a rational application to convince the judge in giving consideration to the decision of the Religious Court. This research is based on case study normative law research by examining the Rantauprapat Religious Court Decision Number 62/Pdt.P/2017/PA.Rap. Types of Qualitative research. The results of the discussion on the dispensation of minors have the basis that they are allowed to marry in accordance with Article 7 paragraph (1) of Law no. 1 of 1974 states "Marriage is only permitted if the man has reached the age of 19 (nineteen) years and the woman has reached the age of 16 (sixteen) years. However, in the provisions of paragraph (2) of Law No.1 of 1974 states "In the case of deviations from paragraph (1) of this article, you can request a dispensation from the Court or other official appointed by both male and female parents. Dispensation for minors can be applied to the Religious Courts on the basis of strong arguments solely to make marriage a harmonious relationship in the survival of a household. In his judgment, the judge is right and correct in giving the decision on the determination of the dispensation of minors, in accordance with the guidelines of the applicable laws and regulations.